Application of nurse‐led CINV management scheme based on risk assessment in breast cancer patients - Yun Ning; Liuliu Zhang; Xiaoxu Zhi; Yun Zhao; Ying Fang; Bing Wu; Zhujie Xu; Lixin Huang; Yi Pei (Precision Medical Sciences)
Abstract Background As one of the common adverse reactions after chemotherapy in breast cancer patients, chemotherapy‐induced nausea and vomiting (CINV) seriously affects the quality of life of breast cancer patients. Objective To explore the application effect of nurse‐led CINV management scheme based on risk assessment in breast cancer patients. Methods The researchers selected 90 breast cancer patients who received chemotherapy at Jiangsu Cancer Hospital from June 1, 2022, to June 1, 2023. The patients were divided into control group and intervention group. The control group implemented the routine nursing mode, and the intervention group implemented the nurse‐led intervention program based on risk assessment. On this basis, the intervention group applied the symptom management theory to the construction of intervention strategy to compare the CINV situation, quality of life, and psychological distress level between the two groups. Results The frequency of vomiting and the degree of nausea in the delayed stage were lower in the intervention group than in the control group, and the difference was statistically significant (p<.05). The life function index of nausea and vomiting in acute stage and delayed stage was higher in the intervention group than in the control group, and the differences were statistically significant (p<.05). The psychological pain scores of the two groups in the acute stage and the delayed stage were lower in the intervention group than in the control group, and the differences were statistically significant (p<.05). Conclusion Nurse‐led CINV management scheme based on risk assessment can effectively reduce the frequency of vomiting, reduce the degree of nausea, improve the quality of life, and alleviate psychological pain in breast cancer patients.